Critical Illness-Related Corticosteroid Insufficiency in Cardiogenic Shock Patients: Prevalence and Prognostic Role. Issue 4 (October 2018) - Ducrocq, Nicolas; Biferi, Pascal; Girerd, Nicolas; Latar, Ichraq; Lemoine, Simon; Perez, Pierre; Thivilier, Carine; Levy, Bruno; Kimmoun, Antoine
ABSTRACT: Background: Cardiogenic shock shares with septic shock common hemodynamic features, inflammatory patterns, and most likely similar complications such as critical illness-related corticosteroid insufficiency. The aim of this study was to evaluate the prevalence of critical illness-related corticosteroid insufficiency in cardiogenic shock patients and to secondarily assess its prognostic value on 90-day mortality. Methods: A single-center prospective observational study conducted over a 3-year period and including all patients with cardiogenic shock. Main exclusion criteria were patients with prior cardiac arrest, sepsis, ongoing corticosteroid therapy, and etomidate administration. A short corticotropin test was performed in the first 24 h following admission. Serum cortisol levels were measured before (T0) and 60 min (T60) after administration of 250 μg of cosyntropin. Critical illness-related corticosteroid insufficiency was defined according to the 2017 consensus definition (basal total cortisol<10 μg·dL −1 or a delta cortisol T60-T0<9 μg·dL −1 ) as well as the thresholds published in 2016 in cardiogenic shock patients associated with worst prognosis (basal total cortisol>29 μg·dL −1 and delta cortisol T60-T0<17 μg·dL −1 ). Results: Seventy-nine consecutive patients hospitalized in intensive care for cardiogenic shock met the inclusion criteria. Overall mortality was 43% at day 90. Forty-two percent had critical illness-related corticosteroid insufficiency using the 2017 consensus definition and 32% using the 2016 cardiogenic shock thresholds. Presence of critical illness-related corticosteroid insufficiency was not an independent factor associated with 90-day mortality irrespective of the thresholds used. Conclusion: Critical illness-related corticosteroid insufficiency is a frequent occurrence in medical cardiogenic shock. However, in this study, such insufficiency was not associated with prognosis. Abstract : Supplemental Digital Content is available in the text